Interfacial Synthesis of Layer-Oriented 2D Conjugated Metal-Organic Framework Films toward Directional Charge Transport - Wang, Zhiyong; Walter, Lisa S.; Wang, Mao; St Petkov, Petko; Liang, Baokun; Qi, Haoyuan; Nguyen Ngan Nguyen; Hambsch, Mike; Zhong, Haixia; Wang, Mingchao; Park, Sangwook; Renn, Lukas; et al. (Journal of the American Chemical Society, 2021)
The development of layer-oriented two-dimensional conjugated metal-organic frameworks (2D c-MOFs) enables access to direct charge transport, dial-in lateral/vertical electronic devices, and the unveiling of transport mechanisms but remains a significant synthetic challenge. Here we report the novel synthesis of metal-phthalocyanine-based p-type semiconducting 2D c-MOF films (Cu2[PcM-O8], M = Cu or Fe) with an unprecedented edge-on layer orientation at the air/water interface. The edge-on structure formation is guided by the preorganization of metal-phthalocyanine ligands, whose basal plane is perpendicular to the water surface due to their π-πinteraction and hydrophobicity. Benefiting from the unique layer orientation, we are able to investigate the lateral and vertical conductivities by DC methods and thus demonstrate an anisotropic charge transport in the resulting Cu2[PcCu-O8] film. The directional conductivity studies combined with theoretical calculation identify that the intrinsic conductivity is dominated by charge transfer along the interlayer pathway. Moreover, a macroscopic (cm2 size) Hall-effect measurement reveals a Hall mobility of ∼4.4 cm2 V-1 s-1 for the obtained Cu2[PcCu-O8] film. The orientation control in semiconducting 2D c-MOFs will enable the development of various optoelectronic applications and the exploration of unique transport properties.
CRIS-Team Scopus Importer:2022-04-14